Model Pembelajaran Matematika Siswa Kelas Satu Sekolah Dasar - - Frengky (Faculty of Psychology, Universitas Gadjah Mada, 2008)
Optimizing school quality depends on the comprehension to teaching‐learning processes in the classroom as well as outside classroom. Quality school shows high capacity in optimizing students’ ability in certain courses such as in mathematics. The teaching‐learning processes of Mathematics, well‐known as a difficult course among students, needs more attention. This study focused on the observation of the teaching learning processes in Mathematics among first grade students of yunior high‐school. The study used a qualitative approach with a grounded theory. Participants were recruited from a yunior high‐school in Yogyakarta. The results showed that students were interested in studying mathematics and consistent guidances were needed in teaching mathematics for students.